PERENCANAAN MEKANISTIK TEBAL PERKERASAN MENGGUNAKAN PROGRAM mePads - Ida Rumkita S; Siegfried Siegfried (Jurnal Jalan-Jembatan, 2006)
Pavement design using mechanistics approach has developed rapidly since a few decades ago. This sort of methods has been a choice because it is very efficient and effective as well as figure out the real condition of pavement system. Using this program, ones can vary type of materials that is possibly used for the pavement system. Currently, many computer programs are available for mechanistic approach which one of them is mePads. This paper tries to detail the effectivity and efficiency of using mePads for pavement design. It is found that this program is very useful for researchers who deal with the stresses and strains in pavement system. Another finding is that the design using mePads is a bit conservative compared to that of AASHTO’93